24‐Month HIV‐free survival among HIV‐exposed Infants in Lesotho: the PEAWIL cohort study. Issue 12 (12th December 2020) - Tukei, Vincent J; Machekano, Rhoderick; Gill, Michelle M; Tiam, Appolinaire; Mokone, Majoalane; Isavwa, Anthony; Nyabela, Malijane; Mots'oane, Tsietso; Nchephe, Seipati; Letsie, Mosilinyane; Kassaye, Seble G; Guay, Laura
Abstract: Introduction: Following the implementation of the provision of lifelong antiretroviral therapy to all HIV‐positive pregnant or breastfeeding women for prevention of mother‐to‐child transmission (PMTCT) of HIV by the Kingdom of Lesotho in 2013, we assessed the effectiveness of this approach by evaluating 24‐month HIV‐free survival among HIV‐exposed infants (HEIs). Methods: We conducted a prospective observational cohort study that enrolled HIV‐positive and HIV‐negative pregnant women, with follow‐up of women and their infants for 24 months after delivery. Participant recruitment started in June 2014 and follow‐up ended in September 2018. Trained nurses collected study information through patient interviews and chart abstraction at enrolment and every three to six months thereafter. Maternal HIV testing, infant mortality, HIV transmission and HIV‐free survival rates were computed using Kaplan–Meier estimation. Cox regression hazard models were used to identify factors associated with infant HIV infection and death. Results: Between June 2014 and February 2016, we enrolled 653 HIV‐positive and 941 HIV‐negative pregnant women. Twenty‐seven HIV‐negative women acquired HIV during follow‐up. Ultimately, 634 liveborn HEI (382 (52%) male, 303 (48%) female, 3 missing) and 839 who remained HIV‐unexposed (HUIs) (409 (49.0%) male, 426 (51.0%) female, 4 missing) were followed; 550 HEIs and 701 HUIs completed the 24‐month follow‐up period. Of 607 (95.7%) HEIs who were tested for HIV at least once during follow‐up, 17 were found to be HIV‐positive. Two (9.5%) of 21 infants born to mothers who acquired HIV infection during follow‐up were HIV‐positive compared to 15 (2.4%) of 613 HEI born to women with known HIV infection. The risk of HIV transmission from HIV‐positive mothers to their infants by 24 months of age was 2.9% (95% CI: 1.8 to 4.7). The estimated 24‐month mortality rate among HEIs was 6.0% (95% CI: 4.4 to 8.2) compared to 3.8% (95% CI: 2.6 to 5.3) among HUIs (Log‐rank p = 0.065). HIV‐free survival at 24 months was 91.8% (95% CI: 89.2 to 93.7). Lower maternal age and birth weight were independently associated with increased HIV infection or death of infants. Conclusions: The implementation of lifelong ART for PMTCT in the Lesotho public health system resulted in low HIV transmission, but survival of HEI remains lower than their HIV uninfected counterparts.